Study of optimality and fairness of different types of electrical power billing mechanisms - Tan, Benedict En Ming (2018)
Autonomous demand response (DR) programs are scalable and result in a minimal control overhead on utilities. The idea is to equip each user with an energy consumption scheduling (ECS) device to automatically control the user’s flexible load to minimize his energy expenditure, based on the updated electricity pricing information. While most works on autonomous DR have focused on coordinating the operation of ECS devices in order to achieve various system-wide goals, they fail to address the important issue of fairness. That is, while they usually guarantee optimality, they do not ensure that the participating users are rewarded according to their contributions in achieving the overall system’s design objectives. Similarly, they do not address the important problem of co-existence when only a sub-set of users participate in a deployed autonomous DR program. In this project, different types of billing mechanisms will be studied and a new billing mechanism will be designed to better achieve fairness.